Prediksi Kerawanan Banjir di Daerah Aliran Sungai Olaya Kabupaten Parigi Moutong - Rivai, R.; Tunas, I.G.; Mardin, R. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
This study aims to determine the distribution of flood vulnerability levels in the Olaya Watershed located in Parigi Moutong Regency, using two previous research methods, namely the Hamdani et al. method, and the Latue & Latue method, which were then validated in the field to determine the level of validity of the two methods. The method used is data collection such as rainfall data, flood incident data, Olaya Watershed maps, DEMNAS maps, soil type maps and spot 6 satellite image maps. The analysis carried out in this study includes classifying and scoring the classification of rainfall parameters, slope gradient, land use, soil type, river buffer, elevation and Overlay is carried out by combining all input flood vulnerability parameters that have been mapped, to obtain flood vulnerability values and flood vulnerability level maps. The results of this study are the results of the analysis of flood vulnerability levels using the Hamdani et al. method, divided into Most Safe, Threatened, Vulnerable and Most Vulnerable while the Latue & Latue method is divided into Low, Medium and High. The results of these two methods are not yet in accordance with the flood events in the Olaya Watershed, this is because the weight of each parameter is not yet appropriate, there are still parameters that have not been included in the flood vulnerability modeling, the scoring of the parameter classification is not yet appropriate and the classification and scoring of the parameters are different